A study on the correlations between parent–child interaction, school adaptation type, and adolescent mental health - Yin Xinqian; Wang Yan; Qu Yashan; Luo Lanlan (Frontiers in Psychology, 2026)
Introduction This study aimed to explore the associations between different parent–child interaction patterns, school adjustment types, and multidimensional mental health indicators such as adolescent wellbeing indices and depressive symptoms and thereby provide insights for improving adolescent mental health. Methods Using questionnaire data from the China Education Panel Survey (CEPS) conducted from spring 2014 to spring 2015, this study focused on school-attending adolescents aged 12–18 years. Data from the Parent–Child Interaction Questionnaire, the School Adjustment Questionnaire, and the Mental Health Questionnaire were used. Cluster analysis using the K-means algorithm, combined with non-parametric tests and the analysis of variance (ANOVA) with multiple comparisons, identified distinct parent–child interaction patterns and school adjustment types and examined their associations with adolescent wellbeing indices and depressive symptoms. Results Depressive symptoms showed negative correlations with positive school adaptation, parent–child interaction frequency, and parent–child interaction content ( r = −0.247, −0.123, −0.16, p < 0.001), while wellbeing exhibited positive correlations ( r = 0.304, 0.135, 0.123, p < 0.001). Parental interaction patterns were categorized into high-frequency (35%), medium-frequency (38%), and low-frequency (27%) groups. School adaptation types were classified as high-involvement adaptation (50%), balanced adaptation (35.3%), and alienated adaptation (15%). Different parent–child interaction patterns significantly influenced adolescents’ mental health (depression: F = 743.821, p < 0.001, ηp 2 = 0.083; wellbeing: F = 795.63, p < 0.001, ηp 2 = 0.079). Different school adaptation types also significantly influenced adolescents’ mental health (depression: F = 135.777, p < 0.001, ηp 2 = 0.022; wellbeing: F = 190.848, p < 0.001, ηp 2 = 0.016). Multiple comparison analyses revealed significant differences between different parent–child interaction patterns and school adaptation factors in their prediction of adolescent mental health outcomes. The predictive effect on the wellbeing index was ΔR 2 = 0.087 ( F = 761.6, p < 0.001), while the predictive effect on depressive symptoms was ΔR 2 = 0.064 ( F = 529.3, p < 0.001). Conclusion The combination of high-frequency parent–child interaction and high-investment school adaptation is most conducive to enhancing adolescents’ wellbeing and alleviating depressive symptoms. This finding provides theoretical guidance and empirical evidence for interventions addressing adolescent mental health issues.